(3TQM JSgjd GdahGFO hJcejd GdebGUOs - (3GdMSf Hf bGSe Hf YHO Gddg GdeQGOj GdeUQj, HOQ GdOjf CHh eMeO, GHf Ge bGSe , J (B749 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3jHOC HHGH GdaGYd Hbhdg(B: (3hgh GdUaI GdOGdI Ydi aGYd, LGQjI aj GdJPcjQ hGdJCfjK Ydi GdeVGQY s
(3BNQgG (B:s
(3YbOJ GdYSd agh YbjO, HeYfi eYbO, hCYdg GdeQV agh Ydjd HeYfi oeYd, hGddg CYde Je GdLRA GdChd ef TQM GdeQGOj Ydi GdJSgjd hjdjg Chd GdKGfj s
(3fSNI KGdKI JJab aj ChdgG eY Chd GdfSNI GdChdi HGNJdGa jSjQ LOkG aj HYV GdCdaGXs
(3JYGhQ YdjgG CcKQ ef fGSNs
(3HChdgG JedcGJ CbOegG ehQN SfI (B959(3g`s
(3hHgG fXGe GdJYbjHI s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs